Centralidade do dinheiro na espiritualidade neopentecostal - Silva, Drance Elias da (Horizonte, 2008)
This Article is centered, in its reflection, SPIRITUALITY CENTRALIZED IN MONEY. The above-mentioned object money is an instrument in god’s hands, present in Neo-pentecostal churches daily cult. And in such a perspective, it – money – coumponds things arsenal, offered at altar. It is a religious symbol fitting to sew GOD – CHURCH – FAITHFUL vertical rapport . But it is not selected as any object at all in order to take part, as a kind of mediation, in this rapport. Money is not a curse, but, sanctified, when immolated to be offered and to multiply the work of God. Some would tend to say that, the entry into the money into the space of the sacred would be to profane God, to destroy him. Can this be so? The tithe is money. It is something that belongs to God. One perceives a certain Mystic, developed fron a resignification constant process. Symbolical perspective compounds this object, called, nominated money, comprehensive analysis, money that, in neo-pentecostal cult space, increases in inportance and expressiveness in faith regarding to those ones who look for victony, conquest, prosperity.